HYGIENE SANITASI DAN ANALISA PENCEMARAN Salmonella sp. PADA DAGING SAPI OLAHAN (DAGING BURGER) SEBELUM DAN SESUDAH DIGORENG YANG DI JUAL DI KELURAHAN HELVETIA TIMUR KECAMATAN MEDAN HELVETIA KOTA MEDAN TAHUN 2013 - widya nurul putry; devi nuraini santi; indra chahaya (Lingkungan dan Kesehatan Kerja, 2014)
Bacteria of the genus Salmonella sp is the bacteria causing the infection. If ingested into the body and cause symptoms called Salmonellosis. More than 90% incidence of human disease caused by consuming food contaminated with pathogenic bacteria, such as Salmonella and Shigella sp s. there were 60% of cases of poisoning in developed countries, a result of the handling of food is not good and bacterial contamination in food at the point of purchase. This study aims to determine the presence of Salmonella sp. the processed beef (meat burgers) before frying and after frying. Type a descriptive research is to describe the hygiene and sanitation and the contamination of Salmonella sp. the burger meat. Object of this study is the burger meat that is used by five merchants burger. The result showed that none of the burger vendors meet the requirements of hygiene and sanitation vendors selling burger place. Salmonella sp found in sample 2 and sample 4 before being fried and Salmonella sp found in sample 1 after frying Hygiene traders most meet health requerements are merchent 5 and merchent 3. merchents who at least meet the requerment of hygiene are merchant 1 and merchant 2. To consumers to attention to the hygiene of the seller and the place before buying a burger. To The environmental health section of the health department to give traders an appeal to hygiene and sanitation in order to become a better trader. Key words: Hygiene, Sanitation, Burger, Salmonella sp